2016
DOI: 10.1002/arch.21334
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning, Expression Pattern of Multidrug Resistance Associated Protein 1 (Mrp1, Abcc1) Gene, and the Synergistic Effects of Verapamil on Toxicity of Two Insecticides in the Bird Cherry‐oat Aphid

Abstract: The ATP-binding cassette (ABC) transporters are important transmembrane proteins encoded by a supergene family. The majority of ABC proteins are primary active transporters that bind and hydrolyze ATP to mediate the efflux of a diverse range of substrates across lipid membranes. In this study, we cloned and characterized a putative multidrug resistance associated protein 1 (MRP1) from Rhopalosiphum padi encoded by ABCC1. Structural analysis showed that this protein has structural features typical of the ABC tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 68 publications
0
18
0
1
Order By: Relevance
“…The down‐regulation of the nAChR subunits could be a possible mechanism of resistance of R. padi to neonicotinoids, although more studies need to be performed to confirm this mechanism. Previously, we found that the ATP‐binding cassette (ABC) transporter ABCC1 was up‐regulated in the imidacloprid‐resistant R. padi strain, and imidacloprid induced the transcription of ABCC1 , indicating a role of ABCC1 in the efflux of insecticides in R. padi ; nevertheless the precise role of ABCC1 in the insecticide resistance remains to be further determined …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The down‐regulation of the nAChR subunits could be a possible mechanism of resistance of R. padi to neonicotinoids, although more studies need to be performed to confirm this mechanism. Previously, we found that the ATP‐binding cassette (ABC) transporter ABCC1 was up‐regulated in the imidacloprid‐resistant R. padi strain, and imidacloprid induced the transcription of ABCC1 , indicating a role of ABCC1 in the efflux of insecticides in R. padi ; nevertheless the precise role of ABCC1 in the insecticide resistance remains to be further determined …”
Section: Discussionmentioning
confidence: 99%
“…Previously, we found that the ATP-binding cassette (ABC) transporter ABCC1 was up-regulated in the imidacloprid-resistant R. padi strain, and imidacloprid induced the transcription of ABCC1, indicating a role of ABCC1 in the efflux of insecticides in R. padi; nevertheless the precise role of ABCC1 in the insecticide resistance remains to be further determined. 64…”
Section: Discussionmentioning
confidence: 99%
“…Verapamil was used to inhibit the activity of ABC transporters at the protein level to verify if phenotypic changes caused by direct transporter inhibition would be similar to those caused by transcript downregulation. Verapamil is a common pharmacological inhibitor of ABC transporters used to test ABC transporter activity in a variety of organisms, including insects [17][18][19][20][21]23,24,[26][27][28][29][30]. In most species, verapamil produces a synergistic effect with insecticide in both resistant and sensitive populations.…”
Section: Verapamil + Ivermectin Survival Assaysmentioning
confidence: 99%
“…MDR proteins have been intensively studied in humans because upregulation of MDR genes confers the multidrug resistance phenotype to cancer cells [16], but since they are highly conserved between organisms, their function is now being explored with respect to insect defenses against [17][18][19][20][21][22][23], and resistance to [24][25][26][27][28][29][30], insecticides. The development of insecticide resistance is frequently driven by amplified levels of natural defense processes, including those of both detoxification and excretion [31].…”
Section: Introductionmentioning
confidence: 99%
“…Since the cloning of ABCC1 in the early 90s [ 17 , 18 , 19 ], progress has been made towards establishing a functional relationship between ABCC1 and CFTR . For example, functional complementation of dysfunctional CFTR by ABCC1 following chemotherapy that resulted in increased expression of ABCC1 was associated with improved lung function in a CF patient [ 15 ].…”
Section: Introductionmentioning
confidence: 99%